PEMANTAPAN PEMILIHAN PROGRAM KEAHLIAN DAN PELUANG KERJA DI SMK 16 JAKARTA WENNY DESTY FEBRIAN.S.E.,M.M Dr. DIDIN HIKMAH PERKASA: PEMANTAPAN PEMILIHAN PROGRAM KEAHLIAN DAN PELUANG KERJA DI SMK 16 JAKARTA WENNY DESTY FEBRIAN.S.E.,M.M Dr. DIDIN HIKMAH PERKASA - Febrian, Wenny Desty Febrian; Perkasa, Didin Hikmah (Andhara, 2025)
The decision-making process needs to be understood by vocational school graduates when entering college, because through these stages the decisions they will take will be more effective. The emergence of goals is usually motivated by a problem faced by someone. If someone who graduated from SMK wants to continue their studies, it is clear that the student has a goal. In his mind there is a picture of the future that is considered the best, for example being a doctor, manager, gusu, and so on. Goals can be realized when you have completed the study. Therefore, vocational school graduates have a goal to be achieved, namely studying in college. The decision to choose which university to enter is a realization of the achievement of goals. Based on the results in the field in this service, the impact of choosing a major on student learning includes the impact of choosing a major on the student learning process, based on the results of interviews that researchers found students who lacked interest in learning with a lot of material that resulted in learning this subject. the student learning process is less than optimal because many students do not understand arithmetic. Students lack enthusiasm for learning and the student learning process is not optimal. For example, at SMKN 16 Jakarta, the major is accounting. In addition, the impact of choosing majors on the completion of school assignments, in this case there will be many students who are less than optimal in completing their school assignments because students do not understand, many tasks pile up and students are no longer enthusiastic about doing school assignments and students often late in collecting assignments, and finally the impact of choosing a major on student learning outcomes, then later student learning outcomes will not be optimal.